Understanding The Cash Flow Impact on Financial Distress among Hospitality Listed Firms Amidst the Covid-19 Pandemic: The Case of Indonesia - Lady Liesdyana Pratiwi; Ersa Tri Wahyuni; Zaldy Adrianto (PT Mattawang Mediatama Solution, 2024)
This study investigates the relationship between cash flow variables and financial distress among hospitality companies listed on the Indonesian stock market between 2017 and 2022. Analysis focused on Operating Cash Flow (OCF), Investment Cash Flow (ICF), and Financial Cash Flow (FCF) to discern their individual and combined impacts on financial distress. The findings reveal that each cash flow variable—OCF, ICF, and FCF—exerts a significant influence on financial distress when considered independently. This supports hypotheses 1, 2, and 3, signifying their substantial role in shaping the financial health of these companies. Additionally, the collective effect of these cash flow variables, as evidenced by the F-test, demonstrates a noteworthy combined impact on financial distress. In summary, this study highlights the intricate interplay between cash flow dynamics and financial distress among Indonesian-listed private companies. While each cash flow component independently affects financial stability, their cumulative influence significantly determines vulnerability to financial distress. This underscores the critical need for comprehensive cash flow management strategies to mitigate financial risks and ensure sustained financial health in these entities amidst economic uncertainties.